Earnings progression, human capital and incentives: Theory and evidence - Anders Frederiksen (Institute for the Study of Labor (IZA), 2010)
The career prospects of newly recruited employees differ substantially within an organization. The stars experience a considerable growth in earnings; others can hardly maintain their entry salaries. This article sheds light on the mechanisms generating the observed heterogeneity in earnings progression by investigating the effects of on-the-job human capital acquisition, explicit short-run incentives and career concern incentives on earnings progression. The model leads to predictions about the incentive structure and the progression in both cross-sectional and individual earnings which are supported by the empirical analysis based on personnel records from a large bank.
Keywords: J30; J41; M50; 330; Explicit incentives; career concern incentives; performance; earnings dynamics; personnel economics; Einkommen; Lohnstruktur; Erwerbsverlauf; Leistungsanreiz; Berufserfahrung; Theorie; Großbank; Dänemark